Improved tools for the diagnosis of Rift Valley fever and serological evidence of the disease in sheep and goats in the inter-epidemic period in the Zambézia Province, Mozambique - Rutten, Victor P.M.G. (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2012.